Contribuição para o desenvolvimento da atividade aquícola sustentável em reservatórios da União brasileira - Nogueira, Sara Monaliza Sousa (2019)
In Brazil, a fish farm practiced in Union reservoirs has been discouraged from the legal point of view, because of the process of regularization of a very slow enterprise, due to large complex bureaucracy, due to the different competent bodies involved, and expensive. As a result, producers end up giving up investing in the industry, weakening it, or doing so illegally, causing negative impacts on the environment. This research sought a survey of the problems related to the current processes of Environmental Licensing of activity and Federal Water Use Authorization, and development of a model that gathers theories for navigation processes. To this end, 68 questionnaires were applied with key agents of the sector from different regions of the country between December 2016 and August 2017 and a Grounded Theory methodology was used to organize, code and analyze the data collected, and then outlining the model of leading emerging theories. This, in turn, revealed 21 recommendations to unlock and accelerate the current process of regularization. Actions, business, and practices, aquatic practices, attractive and innovative, reducing a large number of illegal enterprises and expanded national production in a more sustainable way.